ANALISIS FORCE MAJEURE PERJANJIAN PENGADAAN PASIR DI MASA PANDEMI COVID-19 - Valdi Ryan Akhdan (2022)
The COVID-19 pandemic has been around for so long. During the COVID-19 pandemic, as it is now, it has had such a huge impact on society. Starting from the declining income of many people caused by not being allowed to leave the house making it difficult for people to work, as well as the Covid-19 causing companies that have Cooperation Agreements to be hampered. The government issued regulations to prevent the spread of the COVID-19 virus, starting from urging people to work/study from home to social distancing, PSBB (Large-Scale Social Restrictions) and PPKM (Enforcement of Community Activity Restrictions). This policy can cause a company that has an agreement to be hampered and experience force majeure. Force majeure is a condition or event that cannot be avoided or prevented, and is beyond the capabilities that can be overcome by the parties to the agreement, which includes natural disasters such as: earthquakes, hurricanes, tsunamis, volcanic eruptions, epidemics, pandemics, fires, mass strikes, riots, wars, reforms, mass chaos. With this condition, an achievement that is in an agreement may not be carried out because one or both parties cannot perform its achievements.